Design, Synthesis and Biological Evaluation of Novel and Potent Protein Arginine Methyltransferases 5 Inhibitors for Cancer Therapy - Yixuan Tang; Shihui Huang; Xingxing Chen; Junzhang Huang; Qianwen Lin; Lei Huang; Shuping Wang; Qihua Zhu; Yungen Xu; Yi Zou (Molecules, 2022)
Protein arginine methyltransferases 5 (PRMT5) is a clinically promising epigenetic target that is upregulated in a variety of tumors. Currently, there are several PRMT5 inhibitors under preclinical or clinical development, however the established clinical inhibitors show favorable toxicity. Thus, it remains an unmet need to discover novel and structurally diverse PRMT5 inhibitors with characterized therapeutic utility. Herein, a series of tetrahydroisoquinoline (THIQ) derivatives were designed and synthesized as PRMT5 inhibitors using GSK-3326595 as the lead compound. Among them, compound 20 (IC50: 4.2 nM) exhibits more potent PRMT5 inhibitory activity than GSK-3326595 (IC50: 9.2 nM). In addition, compound 20 shows high anti-proliferative effects on MV-4-11 and MDA-MB-468 tumor cells and low cytotoxicity on AML-12 hepatocytes. Furthermore, compound 20 possesses acceptable pharmacokinetic profiles and displays considerable in vivo antitumor efficacy in a MV-4-11 xenograft model. Taken together, compound 20 is an antitumor compound worthy of further study.